Mechanistic investigations of polyaza[7]helicene in photoredox and energy transfer catalysis - Rocker, Johannes; Zähringer, Till J. B.; Schmitz, Matthias; Opatz, Till; Kerzig, Christoph (Beilstein Journal of Organic Chemistry, 2024)
Organic photocatalysts frequently possess dual singlet and triplet photoreactivity and a thorough photochemical characterization is essential for efficient light-driven applications. In this article, the mode of action of a polyazahelicene catalyst (Aza-H) was investigated using laser flash photolysis (LFP). The study revealed that the chromophore can function as a singlet-state photoredox catalyst in the sulfonylation/arylation of styrenes and as a triplet sensitizer in energy transfer catalysis. The singlet lifetime is sufficiently long to exploit the exceptional excited state reduction potential for the activation of 4-cyanopyridine. Photoinduced electron transfer generating the radical cation was directly observed confirming the previously proposed mechanism of a three-component reaction. Several steps of the photoredox cycle were investigated separately, providing deep insights into the complex mechanism. The triplet-excited Aza-H, which was studied with quantitative LFP, is formed with a quantum yield of 0.34. The pronounced triplet formation was exploited for the isomerization reaction of (E)-stilbene to the Z-isomer and the cyclization of cinnamyl chloride. Catalyst degradation mainly occurs through the long-lived Aza-H triplet (28 µs), but the photostability is greatly increased when the triplet efficiently reacts in a catalytic cycle such that turnover numbers exceeding 4400 are achievable with this organocatalyst.
Keywords: energy transfer; laser spectroscopy; organocatalyst; photoredox; time-resolved spectroscopy